Exploring Sources and Biogeochemical Dynamics of Dissolved Methane in the Central Bohai Sea in Summer - Zhang, Yong; Chen, Bing; Zhai, Wei-dong (Frontiers in Marine Science, 2020)
To clarify biogeochemical controls of environmental factors on the dynamics of dissolved methane (CH4) in shallow-water coastal oceans, we investigated concentrations, sea-to-air fluxes, and the net cycling rate of CH4 in the central Bohai Sea in summer 2018. During the survey, both summertime stratification and dissolve oxygen deficit were observed. In the surface layer, CH4 concentration ([CH4]) ranged from 3.08 to 10.27 nmol kg−1. The averaged sea-to-air flux was estimated at 6.46 ± 3.32mol m−2 d−1, supporting that the Bohai Sea serves as a source of atmospheric CH4. In the bottom layer, [CH4] ranged from 4.29 to 31.04 nmol kg−1. The downward increase of [CH4] within water column indicated substantial sources of CH4 from seafloor. Based on the complex relationship between saturation ratio of CH4 and dissolved oxygen, three types of CH4 release from the seafloor were identified, including diagenesis of buried organic matters, natural leakage from geological settings, and anthropogenic release from offshore oil/gas development. Saturation ratios of CH4 in bottom waters were positively correlated with stratification degree of the water column. Using a two-layer box model, sedimentary CH4 release rates at two oxygen-deficient stations were estimated to be 56.0–60.8 mol m−2 d−1, which were much higher than the sea-to-air fluxes. The modeling results also indicated that the majority of seafloor released CH4 (> 90%) was consumed in the water column of this shallow-water coastal sea. This is the first comprehensive study on CH4 cycling in the Bohai Sea. This work shows the indicating role of dissolved oxygen in identifying multiple CH4 sources and highlights the dominating effects of water stratification and microbial consumption on local CH4 dynamics.